Proposal of a Novel Index of Abdominal Compliance and the Association With Postoperative Pain After Laparoscopic Inguinal Hernia Repair. Issue 2 (17th April 2022) - Kinoshita, Shoichi; Kawaguchi, Chihiro; Takagi, Tadataka; Ohyama, Takao
Abstract : Background: In laparoscopic surgery, low pneumoperitoneum pressure is reported to reduce pain, which suggests that easing abdominal expansion is crucial for less postoperative pain. However, although abdominal compliance (AC) is associated with the degree of abdominal expansion, the role of AC in pain by pneumoperitoneum is unknown. In this study, we devised a novel index as a surrogate of AC to evaluate the association between AC and postoperative pain in laparoscopic inguinal hernia repair. Materials and Methods: We reviewed 83 patients who underwent elective transabdominal preperitoneal repair from 2019 to 2021 at Heisei Memorial Hospital. Insufflation pressure was set to low pressure (8 mm Hg). The abdominal compliance index [ACI; insufflated intra-abdominal volume (L)/body surface area (m 2 )] was utilized to evaluate the association between AC and postoperative pain. Results: ACI was evaluated in 30 patients. Median ACI was 1.53 (1.00 to 2.48) L/m 2 . Although there was no difference in the average body constitution, the high ACI group (n=15) had significantly higher intra-abdominal volume at 8 mm Hg pressure, compared with the low ACI group (n=15) (3.1 vs. 2.1 L, P <0.0001). The high ACI group had significantly higher pain than the low ACI group on the day of surgery (2.0 vs. 1.0, P =0.006) and the day after (0.8 vs. 0.3, P =0.007). In addition, 46.7% of the patients in the high ACI group experienced pneumoperitoneum-associated pain, whereas patients in the low ACI group experienced incision pain only. Additional analgesics were administered in 53.3% of the high ACI group, compared with 33.3% in the low ACI group. Conclusions: AC was suggested to be a vital factor of postoperative pain after laparoscopic inguinal hernia repair. Patients with high AC may be susceptible to higher pain by pneumoperitoneum, even in low-pressure settings.